Sequestration of simulated carbon dioxide (CO2) using churning cementations waste and fly-ash in a thermo-stable batch reactor (TSBR) - Tiwari S.K.; Giri B.S.; Thivaharan V.; Srivastava A.K.; Kumar S.; Singh R.P.; Kumar R.; Singh R.S. (My University, 2025)
The degrees of mineral carbonation in (a) construction and demolition waste (C&DW) and (b) a mixture of cement and fly ash were studied through a dynamic experimental method to determine the variation in the rate and extent of CO2 sequestration achievable under simulated outdoor conditions. A number of experiments were performed in a self-designed rotating batch reactor by churning the two samples together with CO2, which was passed through the mixtures by using water vapor as the medium of transfer. At an injection flow rate of 1 L/min for CO2, the theoretical extent of carbonation was observed to be 39.1% for the mixture of cement and fly ash and 25% for C&DW. It was further observed that upon increasing the CO2 flow rate to 10 L/min, the carbonation in the mixture of cement and fly ash increased by 37.2% after 15 h of rotation at 60 rounds per hour (rph) for a temperature of 40 °C. Weighing, scanning electron microscopy (SEM), and energy dispersive spectrometry (EDS) were performed for the samples before and after the batch reaction to study the quantitative, qualitative and morphological aspects of the process. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.